Diagnostic discrimination of a novel high-sensitivity cardiac troponin I assay and derivation/validation of an assay-specific 0/1h-algorithm - Koechlin, Luca; Boeddinghaus, Jasper; Lopez-Ayala, Pedro; Nestelberger, Thomas; Wussler, Desiree; Mais, Felix; Twerenbold, Raphael; Zimmermann, Tobias; Wildi, Karin; Köppen, Anne Marie; Miró, Òscar; Martin-Sanchez, F Javier; et al. (The American heart journal, 2023)
BACKGROUND: We aimed to assess the diagnostic utility of the Dimension EXL LOCI High-Sensitivity Troponin I (hs-cTnI-EXL) assay. METHODS: This multicenter study included patients with chest discomfort presenting to the emergency department. Diagnoses were centrally and independently adjudicated by two cardiologists using all available clinical information. Adjudication was performed twice including serial measurements of high-sensitivity cardiac troponin (hs-cTn) I-Architect (primary analysis) and serial measurements of hs-cTnT-Elecsys (secondary analysis) in addition to the clinically used (hs)-cTn. The primary objective was to assess and compare the discriminatory performance of hs-cTnI-EXL, hs-cTnI-Architect and hs-cTnT-Elecsys for acute myocardial infarction (MI). Furthermore, we derived and validated a hs-cTnI-EXL-specific 0/1h-algorithm. RESULTS: Adjudicated MI was the diagnosis in 204/1454 (14%) patients. The area under the receiver operating characteristics curve for hs-cTnI-EXL was 0.94 (95%CI, 0.93-0.96), and comparable to hs-cTnI-Architect (0.95; 95%CI, 0.93-0.96) and hs-cTnT-Elecsys (0.93; 95%CI, 0.91-0.95). In the derivation cohort (n = 813), optimal criteria for rule-out of MI were <9ng/L at presentation (if chest pain onset >3h) or <9ng/L and 0h-1h-change <5ng/L, and for rule-in ≥160ng/L at presentation or 0h-1h-change ≥100ng/L. In the validation cohort (n = 345), these cut-offs ruled-out 56% of patients (negative predictive value 99.5% (95%CI, 97.1-99.9), sensitivity 97.8% (95%CI, 88.7-99.6)), and ruled-in 9% (positive predictive value 83.3% (95%CI, 66.4-92.7), specificity 98.3% (95%CI, 96.1-99.3)). Secondary analyses using adjudication based on hs-cTnT measurements confirmed the findings. CONCLUSIONS: The overall performance of the hs-cTnI-EXL was comparable to best-validated hs-cTnT/I assays and an assay-specific 0/1h-algorithm safely rules out and accurately rules in acute MI. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov number, NCT00470587.
Keywords: troponin I; Troponin I; ROC Curve; troponin T; Troponin T; Humans; biologické markery; ROC křivka; prospektivní studie; lidé; Biomarkers; infarkt myokardu; Myocardial Infarction; Prospective Studies